2015
DOI: 10.1007/s10554-015-0682-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of right and left heart mechanics in patients with chronic thromboembolic pulmonary hypertension before and after pulmonary thromboendarterectomy

Abstract: The aim of the present study was to evaluate of the right and left heart mechanics by two-dimensional (2D) speckle tracking echocardiography (STE) in chronic thromboembolic pulmonary hypertension (CTEPH) patients before and after pulmonary thromboendarterectomy (PTE). A total of 40 consecutive CTEPH patients (mean age 49.3 ± 13.5 years, 27 female) were included. 2D STE was performed in all patients before, and 3 months, after PTE. 12 months of prognostic data were also recorded via the use of telephone calls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
2
0
0
1
Order By: Relevance
“…In accordance with previous studies, we observed a significant reverse geometric remodeling of the right atrium 3 months after PEA, which also could lead to improved RV diastolic filling. Olson N. et al demonstrated that after PEA, also LV systolic myocardial deformation has been demonstrated to improve following effects from improved LV diastolic function; however, the study was limited by a short‐term follow‐up after PEA (9.1 ± 3.9 after) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies, we observed a significant reverse geometric remodeling of the right atrium 3 months after PEA, which also could lead to improved RV diastolic filling. Olson N. et al demonstrated that after PEA, also LV systolic myocardial deformation has been demonstrated to improve following effects from improved LV diastolic function; however, the study was limited by a short‐term follow‐up after PEA (9.1 ± 3.9 after) .…”
Section: Discussionsupporting
confidence: 92%
“…We found a persistent lack of ability to increase RV-EF and RV-GLS during peak exercise before as well as after PEA. Physical capacity over time was improved and correlated directly with improvement in RV performance.In accordance with previous studies, we observed a significant reverse geometric remodeling of the right atrium 3 months after PEA,1,20 which also could lead to improved RV diastolic filling. Olson N. et al demonstrated that after PEA, also LV systolic myocardial F I G U R E 3 Impact of cardiac afterload on right ventricle systolic function was evaluated by two-dimensional echocardiography.…”
supporting
confidence: 92%
“…La función y remodelado ventricular derecho tiene un significativo valor pronóstico en pacientes con HAP 2-3 y técnicas de deformación de imagen permiten una sensible evaluación del remodelado y la función VD 4 . Por otro lado, el remodelado y función auricular derecha (AD) evaluada por ecocardiografía usando speckle tracking 5 y por resonancia nuclear magnética 6 se asocian con eventos clínicos en pacientes con HAP.…”
Section: Conclusion: Higher Galectin-3 Concentrationsunclassified